2019
DOI: 10.1111/nep.13230
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study of end‐of‐life treatment preferences and costs following advance care planning for adults with end‐stage kidney disease

Abstract: ACP was associated with improvements in end-of-life care preferences known and adhered to for people with ESKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Furthermore, person-centered advance care planning is initiated at a time that is optimal for the individual, not in reaction to a health crisis or a change to the illness management plan. A comparative case-control study evaluating a nurse-led advance care planning program for adults on hemodialysis in Melbourne, Australia, found that those who undertook the program were significantly more likely to have their preferences known and adhered to by their treating doctor at their end of life (8). This program demonstrated that a coordinated approach to care facilitated by a trained dialysis nurse, working in collaboration with treating doctors, could uphold a critical, person-centered outcome by enabling preferences to be articulated, documented, and adhered to at the end of life.…”
Section: Examples Of Person-centered Care In Ckdmentioning
confidence: 99%
“…Furthermore, person-centered advance care planning is initiated at a time that is optimal for the individual, not in reaction to a health crisis or a change to the illness management plan. A comparative case-control study evaluating a nurse-led advance care planning program for adults on hemodialysis in Melbourne, Australia, found that those who undertook the program were significantly more likely to have their preferences known and adhered to by their treating doctor at their end of life (8). This program demonstrated that a coordinated approach to care facilitated by a trained dialysis nurse, working in collaboration with treating doctors, could uphold a critical, person-centered outcome by enabling preferences to be articulated, documented, and adhered to at the end of life.…”
Section: Examples Of Person-centered Care In Ckdmentioning
confidence: 99%
“…We built the model to run over the last 12-months of life because this was considered the time in which the costs and effects of ACP would be incurred. The decision pathway included the probability of death due to dialysis withdrawal or death due to other causes because past studies of ACP in ESKD indicate that the probability of withdrawing from dialysis is higher for those who complete ACP compared to controls [12, 13]. Furthermore, past qualitative research has shown ACP compels some people with ESKD and their caregivers to change their beliefs and expectations about dialysis [1].…”
Section: Methodsmentioning
confidence: 99%
“…In past empirical studies, ACP has been associated with greater adherence to treatment preferences at end-of-life and greater incidence of patients withdrawing from dialysis in accordance with their preferences compared to controls [12, 13]. However, these findings have not been replicated in large scale, high quality randomized controlled trials [14].…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the prognosis of a patient with CKD is of great importance, and the estimation should comply with several purposes such as resource planning, development of a care plan, informed decision making by the patient, and identification of high risk patients who may benefit from an intervention 3 . In addition, several studies have shown that most patients want to know the prognosis and trajectory of their disease 53 . Furthermore, inadequate information with overly optimistic estimates can trigger unrealistic expectations, frustration, anxiety, depression, and inappropriate aggressive treatments 54 .…”
Section: Prognosticationmentioning
confidence: 99%